2021
DOI: 10.2355/isijinternational.isijint-2020-251
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Iron from Refractory Titanomagnetite by Reduction Roasting and Magnetic Separation

Abstract: The abundant refractory titanomagnetite (TTM) provides a cheap alternative source of iron, but this ore contains impurities and is difficult to process to make suitable concentrates for the blast furnace. In this study, reduction roasting of a primary TTM concentrate followed by magnetic separation was investigated to understand the effects of reduction time, coal dosage, and CaF 2 addition on the reduction behavior of TTM and growth mechanism of iron particles. The phase composition of reduced samples was cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…A similar experiment was carried out by Geng et al [13] and found that the phases in pellets reduced by embedding in the coal were metallic iron, ilmenite and pseudobrookite (FeTi 2 O 5 ). Recently, Zhao et al [21,23] reported that the phases in the reduced mixture consisting of ISC and 25% coal at 1200-1300°C were metallic iron, ilmenite, and anosovite ((Fe,Mg)Ti 2 O 5 ). From the experiments mentioned above, the iron nuggets were not formed, the metallic iron was still attached to other oxides.…”
Section: Nugget Size and Iron Recovery In Nuggetmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar experiment was carried out by Geng et al [13] and found that the phases in pellets reduced by embedding in the coal were metallic iron, ilmenite and pseudobrookite (FeTi 2 O 5 ). Recently, Zhao et al [21,23] reported that the phases in the reduced mixture consisting of ISC and 25% coal at 1200-1300°C were metallic iron, ilmenite, and anosovite ((Fe,Mg)Ti 2 O 5 ). From the experiments mentioned above, the iron nuggets were not formed, the metallic iron was still attached to other oxides.…”
Section: Nugget Size and Iron Recovery In Nuggetmentioning
confidence: 99%
“…[17,21] The addition of sodium sulfate, sodium carbonate and calcium uorite as additives was also investigated to promote the migration, accumulation, and growth of iron into larger particles. [10,13,16,18,23] The nugget formation with a treatment time of 440 min and temperatures up to 1350°C was observed by Hu et al [8] , but in experiments using a laboratory scale rotary hearth furnace at a temperature of 900 -1350°C which was divided into three zones, no nuggets formation was reported [12] .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Alternatively, many studies have focused on direct reduction in the solid-state of TTM by carbonaceous materials wherein iron can be separated from other oxides using magnetic separators 7 23 . Coal as a reducing agent had shown better performance than coke, graphite, or biochar 21 .…”
Section: Introductionmentioning
confidence: 99%
“…More than 1.2 million tonnes of ironsand are mined annually in NZ [7]. Secondly, the ironsand is also regarded as a cheap source of iron units for steel making [8].…”
Section: Background Of the Studymentioning
confidence: 99%